A planning approach for polymetallic mines using a sublevel stoping technique with pillars and ultimate stope limits. Issue 6 (2nd June 2020) - Sari, Yuksel Asli; Kumral, Mustafa
ABSTRACT: A widely used unsupported underground mining technique is sublevel stoping, in which portions of ore-body within certain size constraints are extracted. In this article, a sequential approach is proposed to solve the sublevel determination problem, which is part of development and infrastructure planning, and the stope layout planning problem for polymetallic sublevel stope mining with pillars. First, a new algorithm is proposed to determine the sublevels, which focuses on minimizing the development costs while maintaining access to the profitable portions of the ore-body. Then, the stope layout is planned between the sublevels. A new mixed-integer linear programming formulation for determining the ultimate stope limits is introduced. A case study is conducted on a copper–molybdenum mine to demonstrate the proposed approaches. The results show that the output of the stope layout plan is within the optimal mining limits, which confirms the validity of the approach.